Occurrence of Sperm Abnormality of Beef Cattle at Several Artificial Insemination Centers in Indonesia - Arifiantini, RI; Purwantara, B; Riyadhi, M (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2010)
In the most species studied sperm abnormalities have long been associated with male infertility and sterility. This study evaluated the sperm morphology (normality and abnormality) of beef cattle at several Artificial Insemination centers in Indonesia. Total of 142 bulls were used in this study; an ejaculate from each bull was examined. A drop of semen was placed on 3-4 glass slides, and smears were prepared and air-dried. The smears were stained with carbolfluchsin-eosin (Williams stain). Types of morphological abnormalities were recorded from 500 cells on each sample. It was recorded that 77.46% samples had low primary sperm abnormalities (<5%), while the high level of primary sperm abnormalities (>10%) was found in 5.63% samples. Pear shaped was the most frequently type of abnormality found on examined samples (2.24 ± 2.94%); while double head was the lowest (0.01 ± 0.04%). (Animal Production 12(1): 44-49 (2010) Key words : sperm abnormality, beef catlle, artificial insemination center